Implementation of AI in Animated Health Education Film to Overcome Hospital Anxiety - Rudi Setiawan; Nurhasan Nugroho; Gerald Untirtha Pratama (Brilliance: Research of Artificial Intelligence, 2025)
Children's fear of going to hospitals is a common emotional barrier that can interfere with medical treatment and early health education. This research addresses that issue by developing an animated educational film using artificial intelligence (AI) to help children aged 6–9 overcome their anxiety about medical environments. The purpose of this study is to produce a multimedia-based health education tool that is emotionally engaging, educationally effective, and technically efficient. The film development followed the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. Several AI-based tools were integrated, including ChatGPT for scriptwriting and visual prompting, Kling AI for animation and lip-syncing, ElevenLabs for AI-generated voice-over, and CapCut for final editing. The result is a 7-minute 2D animation titled "Mengatasi Ketakutan Berobat ke Rumah Sakit", which introduces child-friendly characters and a relatable storyline to reduce fear and improve comprehension of hospitals. User testing was conducted on five children aged 8–12, showing a noticeable decrease in hospital-related fear and increased verbal engagement with the topic. Most participants found the animation enjoyable and easy to follow. The findings suggest that AI-supported animation can be an effective medium for health education in children. While the outcome met the expected goals, future research is recommended to include larger participant groups and validated psychological assessment tools for more robust evaluation.